The phenomenon of negative behavior has studied as a social and psychological phenomenon that effect on the performance and life of workers inside and outside the organization. The adoption of this phenomenon is studied in terms of the role of the interna - الطائي, علي حسون; عبد كسار, محمود كاظم (Journal of Economics and Administrative Sciences, 2015)
The phenomenon of negative behavior has studied as a social and psychological phenomenon that effect on the performance and life of workers inside and outside the organization. The adoption of this phenomenon is studied in terms of the role of the internal environment of the organization in addressing this behavior, being the variables belong to the field of organizational behavior to see the results of those variables on the Iraqi organizations, since the specificities of it differ from the rest of the Arab and foreign environments. Therefore, this study focused on testing the relationship of the internal environment of the organization and its role in addressing the negative behavior of the workers.this study came to tested the society of study that represented by (6) offices from the Offices of General Inspectors in the Iraqi Ministries. The sample includes (98) employees, the questionnaire used to collect data and analyzed paragraphs depending on the Statistical Program for Social Sciences (SPSS). The research has come to many conclusions, most notably is, the centralization govern the work of the surveyed Offices of General Inspectors. The workers cannot take the decision by themselves only by reference and in detail to senior management, in spite of knowing what must be done and the limited participation of workers in decision-making by the laws and regulations. The official and complexity limited the free movement of workers towards highlighting the skills and personal abilities that reflected on the functions of the office, standing in front of their ambitions and their inability to embrace new ideas. The administrative leadership affect the negative behaviors, and this shows that the leaders or administrative of offices have prominent role in the treatment of negative behaviors, as it put the plans, policies and programs. It can reflect the vision, philosophy and ideas in creating an appropriate internal environment and encourage their human resources to raise and interact with them and encouraging them to participate in the implementation of these ideas and visions, leading consequently to enhance the trend towards positive behaviors and to move away from the negative ones. The types of positive moral incentives increase the sense of relief and a desire work, as well as a sense of complacency about financial incentives that received being equal to employees in other organizations